Guided Imagery Council: Feasibility, Acceptability, and Preliminary Effects of a Novel Group-Based Lifestyle Intervention in Predominantly Latino Adolescents - Marc J Weigensberg MD; Joseph Provisor MA; Donna Spruijt-Metz PhD; Christianne J Lane PhD; Daniella Florindez MPH; Cheng Wen PhD; Marisa Perdomo PT, DPT; Kim Goodman MSW (SAGE Publishing, 2019)
Background The combination of higher stress and higher obesity rates suggests that Latino youth in the United States may be a population at particular risk for obesity-related adverse health outcomes. The objective of this article is to describe the feasibility, acceptability, and quantitative stress-related outcomes of a 6-week pilot lifestyle intervention using guided imagery (GI) council in order to reduce risk factors for obesity-related disease. Methods Seventeen urban, adolescents (12 females/5 males, 16 Latino, age 17 ± 1 years, grades 9-12, body mass index 22 ± 4) participated in the 6-week, after-school pilot intervention. The intervention consisted of three, 75-minute after-school sessions delivered weekly for 6 weeks. The 3 weekly sessions included 1 session each of nutrition education, physical activity education and practice, and GI delivered in council, a facilitated group process based on indigenous practices. Feasibility and acceptability were assessed by attendance and qualitative exit interview. Stress outcomes included salivary cortisol and perceived stress. Results The pilot intervention was found to be feasible to deliver in an after-school setting. The GI and council group format were well liked. A 31% reduction in salivary cortisol was observed following the stress-reduction GI sessions. Diurnal cortisol patterns did not change across the intervention, but change in perceived stress was correlated with change in cortisol awakening response. Conclusions The intervention was feasible to deliver and highly acceptable. Acute reduction in salivary cortisol was seen following group GI, while no change was seen in daily cortisol patterns. These results support the development of a full 12-week intervention using GI council to reduce obesity-related disease risk.